Molecular detection of Salmonella spp. isolated from apparently healthy pigeon in Mymensingh, Bangladesh and their antibiotic resistance pattern - Saifullah, Md. Khaled; Mamun, Md. Montasir; Rubayet, Reza Md.; Nazir, K. H. M. Nazmul Hussain; Zesmin, Khalada; Rahman, Md. Tanvir (Journal of Advanced Veterinary and Animal Research, 2016)
Objectives: Here we determined the prevalence of Salmonella in cloacal swabs and pharyngeal swabs of apparently healthy pigeons sold in the live bird markets and villages in and around Bangladesh Agricultural University Campus, Mymensingh, Bangladesh. Materials and methods: A total of 50 samples, comprised of cloacal swabs (n=24) and pharyngeal swabs (n=26) were collected. The samples were processed, and Salmonella was isolated through a series of conventional bacteriological techniques and biochemical tests followed by polymerase chain reaction (PCR). Results: The prevalence rate of Salmonella was found to be 37.5% (n=9/24) in cloacal swabs and 30.77% (n=8/26) in pharyngeal swabs with an overall prevalence rate of 34% (n=17/50). The prevalence rate of Salmonella pigeon varied slightly among locations; 34.62% (n=9/26) in live bird markets, and 33.33% (n=8/24) in villages. Molecular detection of 17 Salmonella isolates obtained from biochemical test was performed by genus specific PCR, where all of them amplified a region of 496-bp segment of the histidine transport operon gene. Antibiogram study revealed multi-drug resistant traits in most of the isolates tested. The highest resistance was found against Ampicillin (88.23%) followed by Cephalexin (82.35%). The rate of sensitivity of the isolates to Ciprofloxacin was 100% followed by Azithromycin (82.35%), Gentamicin (76.47%) and Nalidixic acid (76.47%). Conclusion: Our findings suggest that pigeons carry multi-drug resistant Salmonella that may transfer to the humans and animals. http://dx.doi.org/10.5455/javar.2016.c131